Optimalisasi Peran Polisi Masa Depan Oleh Bhabinkamtibmas Sebagai Ujung Tombak Fungsi Pre-Emtif Melalui Aplikasi Elektronik Bhabinkamtibmas (E-Bhabin) Di Polres Bogor - Muhammad Yudisthira Rycko (Indonesian Journal of Police Studies, 2017)
Bhabinkamtibmas is a figure from the concept of the future police that prioritizes prevention efforts in carrying out their duties through pre-emptive functions, and services to the community. The very complex tasks of Bhabinkamtibmas at Bogor Police Precinct have been facilitated with e-bhabin technology. The implementation of e-bhabin still faces many obstacles. This research was conducted aimed at describing the use of e-bhabin, the benefits of supporting the Bhabinkamtibmas task, and the causal factors and efforts that must be made to optimize the use of e-bhabin applications. The study was conducted with a qualitative phenomenological method approach. A qualitative approach to describe the natural setting of the use of e-bhabin application technology support. The focus of this research is service with the use of e-bhabin, factors that cause services, efforts to make services effective. Data taken by observation, in-depth interviews and documentation. Data processed with descriptive analysis. The results showed that the e-bhabin program at Bogor District Police Station had not been running optimally. This happens because of the inconsistent use of the application, SIMAK BMN is not registered so there is no maintenance support from the department, limited facilities and limited competency of officers. Through this program the system of reporting, evaluating and directing leaders, as well as various information can be obtained easily, faster, more accurate data storage, can be accessed by all leaders and members of other functions. Efforts to optimize the e-bhabin program, starting from evaluating and turning on existing applications, make it simple, easy to understand and do, register with SIMAK BMN, conduct periodic outreach and training, all Bhabinkamtibmas, members of other police functions, and members of the community feel the benefits.